INFLUÊNCIA DA ADIÇÃO DE ARGAMASSA ISOLANTE NAS PROPRIEDADES TERMO-FÍSICO-MECÂNICAS DE ARGAMASSAS PARA REVESTIMENTO DE PAREDE - Tavares, Filipe Augusto; Callejas, Ivan Julio Apolonio; Durante, Luciane; Souza, Bruna Guimarães de; Guarda, Emeli Lalesca Aparecida da (ENCONTRO NACIONAL DE TECNOLOGIA DO AMBIENTE CONSTRUÍDO, 2018)
This paper aims to analyze the influence of the incorporation of insulating material in thermal and mechanical properties of mortars used to compose vertical walls. Three mortars were researched: the first one (reference) was composed by cement, hydrated lime and sand in 1:2:8 proportion (in weigh); the second one was obtained adding industrialized thermoinsulating mortar in the previous one, with half in weight being incorporated in the reference mortar; and the third one was obtained according to the proportion indicated by the manufacturer of the industrialized insulating mortar. The incorporation of thermo insulating mortar provided an increase in compressive strength in the order of 115.90% and a decrease in the mean thermal conductivity of 30% in relation to reference mortar. It was concluded that the addition of insulating mortar is technically feasible because it reduced the thermal conductivity of conventional mortar and increased its mechanical strength.